Changing climate yet healthy forest stand of Tsuga dumosa in temperate zone of central Nepal - Chaulagain, Sarita; Aryal, Sugam; Basnet, Saroj; Tiwari, Achyut (Acta Ecologica Sinica, 2023)
Nepal Himalaya is experiencing a faster rate of temperature rise than the global average, and the temperature has altered the growth patterns and distribution of mountain trees. A dendrochronological study was conducted for Tsuga dumosa (D.Don) Eichler to analyze growth-climate relationship from the temperate forest of central Nepal. We developed 116 year-long tree ring width chronology spanning from 1905 to 2020 CE. The study area showed a significant increase in atmospheric temperature and a decrease in rainfall during the past 42 years. It is found that the spring season (March–May) climate is sensitive to the radial growth of T. dumosa. Ring width indices showed a substantial positive correlation with the minimum temperature of January, March, and June of the growth year. Conversely, a negative correlation was observed with the maximum temperature of the previous year's months (July, September, and November), March, and September of the current year, and rainfall during June and November. Basal Area Increment (BAI) trend is positive, indicating the forest is healthy despite the decline in the years 1942, 1978, and 1998. We conclude that the warming of the spring season (March–May), previous year's late growing season and moisture supply (precipitation) during June are critical to the radial growth of Tsuga dumosa in the region. However, responses from multiple species and their exposure to different climate regimes would ideally be required to make predictions on the growth climate relationships of forest trees.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Basal area increment (BAI); Dendroclimatology; Growth-climate response; Tree ring; Tsuga dumosa

“dendRoAnalyst”: A tool for processing and analysing dendrometer data - Aryal, Sugam; Häusser, Martin; Grießinger, Jussi; Fan, Zexin; Bräuning, Achim (Dendrochronologia, 2020)
Dendrometers are vital tools for studying the response of trees to intra-annual environmental changes in different temporal resolutions, ranging from hourly, daily to weekly time resolution. Dendrometers are increasingly used in forest management and tree physiological studies. Besides the data analysis, data processing is also challenging, time-consuming and potentially error-prone due to the immense number of measurements generated by self-registering electronic dendrometers. We present the package ‘dendRoAnalyst’ based on R statistical software to process and analyse dendrometer data using various approaches. This package offers algorithms for handling and pre-cleaning of dendrometer data before the application of subsequent data analytical steps. This includes identifying and erasing artefacts in dendrometer datasets not related to actual stem circumference change, identifying data gaps within records, and the possibility of change(s) in temporal resolution. Furthermore, the package can calculate different daily statistics of dendrometer data, including the daily amplitude of tree growth. The package dendRoAnalyst is therefore intended to facilitate researchers with a collection of functions for handling and analysing dendrometer data.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Dendrometer; R-package; Stem-cycle approach; Stem-variation analysis; Tree-growth monitoring; Zero-growth approach

Drought, temperature, and moisture availability: understanding the drivers of isotopic decoupling in native pine species of the Nepalese Himalaya - Aryal, Sugam; Grießinger, Jussi; Gaire, Narayan Prasad; Bhattarai, Tribikram; Bräuning, Achim (International Journal of Biometeorology, 2024)
The Himalayas experienced long-term climate changes and recent extreme weather events that affected plant growth and the physiology of tree species at high-elevation sites. This study presents the first statistically robust δ18OTR chronologies for two native pine species, Pinus roxburghii, and Pinus wallichiana, in the lower Nepalese Himalaya. The isotope chronologies exhibited 0.88‰ differences in overall mean isotope values attributed to varying elevations (460–2000 m asl). Comparative analysis of climate response using data sets from different sources and resolutions revealed the superiority of the APHRODITE (Asian Precipitation – Highly-Resolved Observational Data Integration Towards Evaluation) data set calibrated for the South Asian Summer Monsoon (SASM)-dominated region. Both species exhibited negative correlations with monsoon precipitation and positive correlations with temperature. However, during the peak monsoon season (July-August), daily resolved climate data disentangled statistically insignificant relationships, and revealed that δ18OTR is influenced by atmospheric moisture. Both congeneric species showed a decoupling between the chronologies after 1995. However, no significant change in air moisture origin and monsoon regime between the study sites was observed, indicating a consistent dominant moisture source during different monsoon seasons. Besides, we also observed the decreased inter-series correlation of both δ18OTR chronologies after 1995, with P. wallichiana experiencing a steeper decrease than P. roxburghii. The weakening correlations between and within the chronologies coincided with a regional drought during 1993–1995 in both sites, highlighting the strong regulation of local climate on the impact of regional extreme climate events. Our findings emphasise the importance of employing climate data with optimal spatial and temporal resolution for improved δ18OTR-climate relationships at the intra-annual scale while considering the influence of site-specific local environmental conditions. Assessing climate data sets with station data is vital for accurately interpreting climate change’s impact on forest response and long-term climate reconstructions.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Isotopic decoupling; Local environmental effects; Native pine species; Nepalese Himalaya; Precipitation; Stable oxygen isotopes; Temperature

GROWTH PATTERN OF PINUS ROXBURGHII UNDER DIFFERENT REGIMES OF INVASIVE SPECIES IN PANCHASE, NEPAL HIMALAYAS - Dyola, Nita; Bhuju, Dinesh Raj; Kharal, Deepak Kumar; Aryal, Sugam; Gaire, Narayan Prasad; Hitler, Louis (Pakistan Journal of Botany, 2020)
Invasive alien species have taken attention as one of the significant threats to biodiversity worldwide. The ongoing climate change is likely to exacerbate the problem by opening up favorable environments for invasion, putting the ecological, environmental and socio-economic state into stake. The assessment of potential impacts of invasive species on native species is crucial for prevention and mitigation measures. Thus, the current study aimed to assess the impact of invasive species (i.e., Ageratina adenophora Sprengel) on the growth of ecologically important native tree species (i.e., Pinus roxburghii Sargent) in Panchase, Nepal Himalaya Furthermore, it explored the dendroecological approach of Pinus roxburghii to assess the potential impacts of invasive species on its growth. The growth pattern was focused on regeneration, tree radial growth and inter-nodal growth rate of saplings and seedlings of Pinus roxburghii under two different classes of invasion i.e., low and high-density. The study revealed that the density and inter-nodal growth rate of seedlings of Pinus roxburghii declined significantly whereas no significant decline occurred in its saplings with the increase in invasion. However, the saplings showed significant increment in its inter-nodal growth rate with the increase in invasion. In the case of its tree, no such significant impact in the radial growth rate was observed. The novel study using dendroecological approach revealed that the invasive species have differential impacts on the growth of nearby native tree species with higher impacts during the seedling stage compared to the saplings and tree stage.
CRIS-Team WoS Importer:2020-02-28

Growth performance of planted population of Pinus roxburghii in central Nepal - Tiwari, Achyut; Thapa, Nita; Aryal, Sugam; Rana, Prabina; Adhikari, Shankar (Journal of Ecology and Environment, 2020)
Background: Climate change has altered the various ecosystem processes including forest ecosystem in Himalayan region. Although the high mountain natural forests including treelines in the Himalayan region are mainly reported to be temperature sensitive, the temperature-related water stress in an important growth-limiting factor for middle elevation mountains. And there are very few evidences on growth performance of planted forest in changing climate in the Himalayan region. A dendrochronological study was carried out to verify and record the impact of warming temperature tree growth by using the tree cores of Pinus roxburghii from Batase village of Dhulikhel in Central Nepal with sub-tropical climatic zone. For this total, 29 tree cores from 25 trees of P. roxburghii were measured and analyzed. Result: A 44-year long tree ring width chronology was constructed from the cores. The result showed that the radial growth of P. roxburghii was positively correlated with pre-monsoon (April) rainfall, although the correlation was not significant and negatively correlated with summer rainfall. The strongest negative correlation was found between radial growth and rainfall of June followed by the rainfall of January. Also, the radial growth showed significant positive correlation with that previous year August mean temperature and maximum temperature, and significant negative correlation between radial growth and maximum temperature (Tmax) of May and of spring season (March-May), indicating moisture as the key factor for radial growth. Despite the overall positive trend in the basal area increment (BAI), we have found the abrupt decline between 1995 and 2005 AD. Conclusion: The results indicated that chir pine planted population was moisture sensitive, and the negative impact of higher temperature during early growth season (March-May) was clearly seen on the radial growth. We emphasize that the forest would experience further moisture stress if the trend of warming temperatures continues. The unusual decreasing BAI trend might be associated with forest management processes including resin collection and other disturbances. Our results showed that the planted pine forest stand is sub-healthy due to major human intervention at times. Further exploration of growth climate response from different climatic zones and management regimes is important to improve our understanding on the growth performance of mid-hill pine forests in Nepal.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Basal area increment (BAI); Radial growth; Tree-rings

Growth ring measurements of Shorea robusta reveal responses to climatic variation - Baral, Sony; Gaire, Narayan Prasad; Aryal, Sugam; Pandey, Mohan; Rayamajhi, Santosh; Vacik, Harald (Forests, 2019)
Many tropical species are not yet explored by dendrochronologists. Sal (Shorea robusta Gaertn.) is an ecologically important and economically valuable tree species which grows in the southern plains and mid-hills of Nepalese Central Himalayas. Detailed knowledge of growth response of this species provides key information for the forest management. This paper aims to assess the dendroclimatic potential of Shorea robusta and to understand climatic effects on its growth. A growth analysis was done by taking 60 stem disc samples that were cut 0.3 m above ground and represented different diameter classes (>10 cm to 50 cm). Samples were collected and analysed following standard dendrochronological procedures. The detailed wood anatomical analysis showed that the wood was diffuse-porous, with the distribution of vessels in the entire ring and growth rings mostly marked with gradual structural changes. The basal area increment (BAI) chronology suggested that the species shows a long-term positive growth trend, possibly favoured by the increasing temperature in the region. The growth-climate relationship indicated that a moist year, with high precipitation in spring (March-May, MAM) and summer (June-September, JJAS), as well as high temperature during winter (November-February) was beneficial for the growth of the species, especially in a young stand. A significant positive relationship was observed between the radial trees increment and the total rainfall in April and the average total rainfall from March to September. Similarly, a significant positive relationship between radial growth and an average temperature in winter (November-January) was noted.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Community forest; Disc; Nepal; Shorea robusta; Tree-ring; Tropical region

Insect infestations have an impact on the quality of climate reconstructions using Larix ring-width chronologies from the Tibetan plateau - Aryal, Sugam; Grießinger, Jussi; Arsalani, Mohsen; Meier, Wolfgang; Fu, Pei Li; Fan, Ze Xin; Bräuning, Achim (Ecological Indicators, 2023)
Insect outbreaks are proven to harm trees, reducing their biomass accumulation due to the defoliation of leaves during the growing season. Various defoliators are responsible for the formation of extremely narrow tree rings in different tree species. In climate reconstructions based on tree-ring width, such narrow rings are often considered as noise, because their formation is not entirely caused by climatic conditions. Thus, the impact of defoliators should be removed (nullified) for unbiased climate reconstructions. This study mainly describes a statistical approach to disentangle the effects of Larch budmoth(LBM) (Zeiraphera diniana) and climate for an unbiased temperature reconstruction in the Bai-Ma mountain area in Southwest China using Larix potaninii. After applying our new approach, growth-climate relationships improved significantly (p < 0.05), especially with minimum temperature during the growing season (June-September). The resulting temperature reconstruction (BTmin) covers the period 1712–2020 CE (313 years). Our final temperature reconstruction for the Bai-Ma area showed a wiggly trend from 1712 to 1980, with some cool periods (1791–1853 and 1888–1930) and warm episodes (1724–1745, 1854–1887, 1950–1967). During the recent 50 years, BTmin reveal an alarming warming trend of up to 0.4 °C per decade. We also observed a strong coherency of BTmin with regional temperature series. Furthermore, we detected a differential effect of various climate modes, with the most substantial impact of the Atlantic Multidecadal Oscillation (AMO) on BTmin (p < 0.01). Interestingly, the Pacific Decadal Oscillation (PDO) showed a coupled effect along with AMO on BTmin. As revealed in this study, removing the LBM effect improved the chronology's climate sensitivity, leading to a more robust transfer function and in terms of insect infestations unbiased climate reconstructions. Thus, it is recommended to check ring-width data for any periodicity potentially related to insect outbreaks and correct the original data before using tree-ring chronologies for climate reconstruction.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Defoliator; Dendrochronology; Larch budmoth; Minimum temperature; Outbreak; Yunnan

INTRAGRO: A machine learning approach to predict future growth of trees under climate change - Aryal, Sugam; Grießinger, Jussi; Dyola, Nita; Gaire, Narayan Prasad; Bhattarai, Tribikram; Bräuning, Achim (Ecology and Evolution, 2023)
The escalating impact of climate change on global terrestrial ecosystems demands a robust prediction of the trees' growth patterns and physiological adaptation for sustainable forestry and successful conservation efforts. Understanding these dynamics at an intra-annual resolution can offer deeper insights into tree responses under various future climate scenarios. However, the existing approaches to infer cambial or leaf phenological change are mainly focused on certain climatic zones (such as higher latitudes) or species with foliage discolouration during the fall season. In this study, we demonstrated a novel approach (INTRAGRO) to combine intra-annual circumference records generated by dendrometers coupled to the output of climate models to predict future tree growth at intra-annual resolution using a series of supervised and unsupervised machine learning algorithms. INTRAGRO performed well using our dataset, that is dendrometer data of P. roxburghii Sarg. from the subtropical mid-elevation belt of Nepal, with robust test statistics. Our growth prediction shows enhanced tree growth at our study site for the middle and end of the 21st century. This result is remarkable since the predicted growing season by INTRAGRO is expected to shorten due to changes in seasonal precipitation. INTRAGRO's key advantage is the opportunity to analyse changes in trees' intra-annual growth dynamics on a global scale, regardless of the investigated tree species, regional climate and geographical conditions. Such information is important to assess tree species' growth performance and physiological adaptation to growing season change under different climate scenarios.
CRIS-Team Scopus Importer:2023-11-03
Keywords: dendrometer; growing-season change; intra-annual growth; machine learning algorithm; Pinus roxburghii; sub-tropical Nepal

Linking leaf elemental traits to biomass across forest biomes in the Himalayas - Dyola, Nita; Liang, Eryuan; Peñuelas, Josep; Camarero, J. Julio; Sigdel, Shalik Ram; Aryal, Sugam; Lin, Wentao; Liu, Xiang; Liu, Yongwen; Xu, Xingliang; Rossi, Sergio (Science China-Earth Sciences, 2024)
Plants require a number of essential elements in different proportions for ensuring their growth and development. The elemental concentrations in leaves reflect the functions and adaptations of plants under specific environmental conditions. However, less is known about how the spectrum of leaf elements associated with resource acquisition, photosynthesis and growth regulates forest biomass along broad elevational gradients. We examined the influence of leaf element distribution and diversity on forest biomass by analyzing ten elements (C, N, P, K, Ca, Mg, Zn, Fe, Cu, and Mn) in tree communities situated every 100 meters along an extensive elevation gradient, ranging from the tropical forest (80 meters above sea level) to the alpine treeline (4200 meters above sea level) in the Kangchenjunga Landscape in eastern Nepal Himalayas. We calculated community-weighted averages (reflecting dominant traits governing biomass, i.e., mass-ratio effect) and functional divergence (reflecting increased trait variety, i.e., complementarity effect) for leaf elements in a total of 1,859 trees representing 116 species. An increasing mass-ratio effect and decreasing complementarity in leaf elements enhance forest biomass accumulation. A combination of elements together with elevation explains biomass (52.2% of the variance) better than individual elemental trait diversity (0.05% to 21% of the variance). Elevation modulates trait diversity among plant species in biomass accumulation. Complementarity promotes biomass at lower elevations, but reduces biomass at higher elevations, demonstrating an interaction between elevation and complementarity. The interaction between elevation and mass-ratio effect produces heterogeneous effects on biomass along the elevation gradient. Our research indicates that biomass accumulation can be disproportionately affected by elevation due to interactions among trait diversities across vegetation zones. While higher trait variation enhances the adaptation of species to environmental changes, it reduces biomass accumulation, especially at higher elevations.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Ecosystem function; Elevational gradient; Functional diversity; Functional traits; Leaf elements; Niche complementarity

Species richness is a strong driver of forest biomass along broad bioclimatic gradients in the Himalayas - Dyola, Nita; Sigdel, Shalik Ram; Liang, Eryuan; Babst, Flurin; Camarero, J. Julio; Aryal, Sugam; Chettri, Nakul; Gao, Shan; Lu, Xiaoming; Sun, Jian; Wang, Tao; Zhang, Gengxin; et al. (Ecosphere, 2022)
Forest biomass is an important component of terrestrial carbon pools. However, how climate, biodiversity, and structural attributes co-determine spatiotemporal variation in forest biomass remains not well known. We aimed to shed light on these drivers of forest biomass by measuring diversity and structural attributes of tree species in 400-m2 plots located every 100 m along a 4200-m elevational gradient in the eastern Himalayas. We applied structural equation models to test how climate, species richness, structural attributes, and their interactions influence forest biomass. Importantly, species richness was a stronger driver of biomass than environmental and structural attributes such as annual air temperature or stem density. Integrating the availability of energy and the demand for water, potential evapotranspiration was more strongly correlated with biomass than water availability, likely due to the strong influence of the Indian summer monsoon. Thus, interactions between climate and tree community composition ultimately control how much carbon is stored in woody biomass across bioclimatic gradients. This fundamental understanding will support predictive efforts of the forest carbon sink in this hydroclimatically important region and help preserving regional forests as a potent natural solution for climate change mitigation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: alpine treeline; carbon; climate; diversity; elevation; potential evapotranspiration; tropical forest

Spring season in western nepal himalaya is not yet warming: A 400-year temperature reconstruction based on tree-ringwidths of Himalayan Hemlock (Tsuga Dumosa) - Aryal, Sugam; Gaire, Narayan Prasad; Pokhrel, Nawa Raj; Rana, Prabina; Sharma, Basant; Kharal, Deepak Kumar; Poudel, Buddi Sagar; Dyola, Nita; Fan, Ze Xin; Grießinger, Jussi; Bräuning, Achim (Atmosphere, 2020)
The Himalayan region has already witnessed profound climate changes detectable in the cryosphere and the hydrological cycle, already resulting in drastic socio-economic impacts. We developed a 619-yea-long tree-ring-width chronology from the central Nepal Himalaya, spanning the period 1399-2017 CE. However, due to low replication of the early part of the chronology, only the section after 1600 CE was used for climate reconstruction. Proxy climate relationships indicate that temperature conditions during spring (March-May) are the main forcing factor for tree growth of Tsuga dumosa at the study site. We developed a robust climate reconstruction model and reconstructed spring temperatures for the period 1600-2017 CE. Our reconstruction showed cooler conditions during 1658-1681 CE, 1705-1722 CE, 1753-1773 CE, 1796-1874 CE, 1900-1936 CE, and 1973 CE. Periods with comparably warmer conditions occurred in 1600-1625 CE, 1633-1657 CE, 1682-1704 CE, 1740-1752 CE, 1779-1795 CE, 1936-1945 CE, 1956-1972 CE, and at the beginning of the 21st century. Tropical volcanic eruptions showed only a sporadic impact on the reconstructed temperature. Also, no consistent temperature trend was evident since 1600 CE. Our temperature reconstruction showed positive teleconnections with March-May averaged gridded temperature data for far west Nepal and adjacent areas in Northwest India and on the Southwest Tibetan plateau. We found spectral periodicities of 2.75-4 and 40-65 years frequencies in our temperature reconstruction, indicating that past climate variability in central Nepal might have been influenced by large-scale climate modes, like the Atlantic Multi-decadal Oscillation, the North Atlantic Oscillation, and the El Nino-Southern Oscillation.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Climate variability; Dendroclimatology; Manang; Past climate; Pre-monsoon temperature

Xylem formation patterns from Mediterranean to subalpine climate conditions reveal high growth plasticity of pine species on Corsica - Häusser, Martin; Aryal, Sugam; Barth, Johannes; Bendix, Joerg; Garel, Emilie; van Geldern, Robert; Huneau, Frederic; Juhlke, Tobias; Knerr, Isabel; Santoni, Sebastien; Szymczak, Sonja; Trachte, Katja; et al. (Trees-Structure and Function, 2023)
Key messageBlack pine and Maritime pine exhibit considerable differences in growth phenology across elevation belts with a 1-month delay for xylogenesis and increasing growth rates from low, mid to high elevations.Investigating seasonal wood formation is crucial to understand tree growth responses to climate impact. The present study quantifies the variability of xylogenesis along an elevation gradient on the Mediterranean island of Corsica, where two native pine species (Pinus nigra Arnold ssp. laricio Maire and Pinus pinaster Aiton) grow from the upper tree line to sea level, partly in sympatry. We extracted microcores from 35 trees at 5 sites along an East-West transect from the coasts (10 m asl) to the island's central mountain ridge (1600 m asl) during bi-weekly sampling campaigns between 2017 and 2019. We applied generalised additive models to detect radial growth differences in elevation and species along with minimum temperatures for growth initiation. We found that trees in low elevations experienced over 2 months longer growth periods with higher maximum growth rates than in high elevations. The results show a 1-month delay for the beginning of tracheid formation between the low, mid and high-elevation belts but comparable timing for its termination. At the sites where both species co-occur, P. nigra accumulates more radial cells in a shorter time than P. pinaster. Trees at the two contrasting coastal sites have similar growth period lengths, but exhibit a time shift of over a month. Minimum temperatures around growth initiation vary between 3.1 degrees C for P. nigra and 9.9 degrees C for P. pinaster. These findings emphasise the high plasticity in the growth behaviour of one of the most widespread tree genera in Mediterranean and temperate zones.
CRIS-Team WoS Importer:2023-04-07